Perbandingan Korelasi - Regresi Berat Badan Terhadap Tinggi Badan dengan Parameter Benn - Wiwid Wahyudi; Idha Yunianto (Saturnus: Jurnal Teknologi dan Sistem Informasi, 2024)
A study was conducted to identify the relationship between height and weight. A researcher claimed that on average, when height increases, weight increases. This is called the Benn parameter. Weight can be adjusted for height using the Benn parameter (kg/mB), where B is the power that minimizes the correlation with height. To investigate how the Benn parameter changes across age and differs between genders. Using linear regression. Multilevel modeling was used to develop a history showing how Benn's parameters change with age from childhood through mid-adulthood and into older age. The data used information from a sample of 40 adults and 40 children under five. Height was measured in centimeters, weight was measured in kilograms. At alpha equal to 0.05 (α=0.05), the hypothesis is that there is a relationship between height and weight. This is the data, which is height and weight. And here is the hypothesis. (Hnull) there is no relationship between height and weight, ρ equals 0. And ,, there is a relationship between height and weight, ρ does not equal 0. And we test to claim that .